A CRITICAL REVIEW OF CONTAGION RISK IN BANKING. (24th July 2012) - Hasman, Augusto
Abstract The recent financial crisis has focused the attention of scholars and policymakers on how to improve financial stability through better macro‐prudential regulation and supervision. In this paper, we compare the existing theoretical and empirical literature on contagion through the banking system. It is argued that the structure of the interbank market, the size of banks, the linkages among them, the level of correlation of their investments and the transparency of the regulator are key factors in determining the possibility of contagion. We discuss the different findings and present avenues for future research.